(untitled) (Orchid Academia Siraha, 2024)
The main objective of this paper is to describe the condition of teaching social studies in secondary level, and identify the problems of it. Sampling of schools, teachers, head teachers and students was done purposefully. This paper has tried to analyze the use of teaching planning, use of teaching methods, availability of teaching materials, evaluation process, use of information and technology, situation of teachers of social studies of secondary level through interview and observation. Most of the studied schools were found suffering from the unavailability of teaching materials. Similarly, overcrowded classes, lack of desk-benches, lack of training for the teachers, teaching without lesson plan were the problems found in the study.